The Role of the Audit Committee as a Mediating Variable on Audit Quality - Rahayu, Nurul; Rochmatullah, Mahameru Rosy (E-Jurnal Akuntansi, 2024)
This study intends to examine the aspects that can affect audit quality by applying the Structural Equation Model (SEM) approach through WarpPLS 7.0. The variables considered include audit tenure, audit fee, audit delay, audit rotation and audit committee also acts as a mediating variable. The research sample consists of 74 observations collected from 16 business entities listed on the Indonesia Stock Exchange from 2016 to 2022 through purposive sampling technique. The results of the direct effect analysis show that audit tenure, audit fees, audit delay and audit rotation do not show a significant correlation with audit quality. However, the audit committee shows a significant correlation with audit quality. And the results of the indirect effect analysis mediated by the audit committee show that audit tenure and audit rotation also do not show a significant correlation. While audit fees and audit delay show a significant correlation. Keywords: Audit Quality; Audit Tenure; Audit Fee; Audit Delay; Audit Rotatin